Bio-removal of phenanthrene, 9-fluorenone and anthracene-9, 10-dione by laccase from Aspergillus niger in waste cooking oils. (November 2019) - Teng, Chong; Wu, Shimin; Gong, Guangyi
Abstract: In this study, we have investigated the effect of laccase from Aspergillus niger on the oxidation indices and polycyclic aromatic hydrocarbon (PAH) and oxygenated PAH (OPAH) content in waste cooking oil after frying nugget, pumpkin pie and youtiao. The acid value remained almost same while the peroxide value saw increment ranging from 423.80% to 993.00% in different samples after 48 h of enzymatic incubation. The concentration of phenanthrene, 9-fluorenone and anthracene-9, 10-dione detected in our samples were respectively 55.52–62.57, 15.82–23.24 and 14.99–27.50 μg/kg and they were removed by a maximum of 18.31%, 26.92% and 19.41% after 24 h and 29.24%, 70.02% and 62.88% after 48 h. The removal ratio was higher with prolonged experiment duration. We also deduced the respective degradation pathway of these compounds. The result suggests that laccase could be used for green-removal of specified PAH and OPAH in waste cooking oil. Highlights: POV in waste cooking oils increased significantly after 48 h of laccase incubation. AV in waste cooking oils remained constant during the laccase treatment. Phe, ATQ and 9FO in waste cooking oils were significantly reduced by laccase. The degradation rate of Phe, ATQ and 9FO increased with reaction time within 48 h.